Concept of Human Development Index on the Qur'an Perspective - Mardianto, Dedi (Journal of Modern Islamic Studies and Civilization, 2025)
This research focuses on the reinterpretation of the concept of the Human Development Index in the perspective of the Qur'an, especially through the study of Surah An-Nahl verse 97, so that the main purpose of this research is to reformulate the conceptual framework of the Human Development Index by basing the indicators of education, health, and decent living standards according to the Qur'anic values which are analyzed through qualitative methods with a library research approach and tafsir methods thematic (maudhu'i) to analyze the verses of the Qur'an that are relevant to human development. The results of the study show that the main values in HDI education, health, and welfare have normative reinforcement in the Qur'an, including in Q.S. Al-Mujādilah verse 11 (education), Q.S. Al-Baqarah verse 195 (health), and Q.S. Al-Hasyr verse 7 (distribution of welfare). These three dimensions are contained in the concept of ḥayātan ṭayyibah which is interpreted as a quality life, balanced between this world and the hereafter, and based on faith and righteous deeds. Therefore, it is necessary to integrate modern development policies with ethical and spiritual principles in Islam.